Analisis Perbandingan Kinerja Keuangan Pada Bank Umum Konvensional Dengan Bank Umum Syariah Menggunakan Metode REC Dan EVA Tahun 2018-2022 - Rasyidah, Milatul; Zulkifli, Makhmud (Jurnal Kajian Ilmu Manajemen (JKIM), 2024)
This research aims to determine the comparison of financial performance between Conventional Commercial Banks and Sharia Commercial Banks in Indonesia using the REC and EVA methods in 2018 – 2022. The aspect examined in this research is the Risk Profile aspect which is measured using the NPL and LDR ratio. The Earnings aspect is measured using the ROA, NIM and BOPO ratios. The capital aspect is measured using the CAR ratio and using EVA measurements. The sample was selected using a purposive sampling method so that 7 BUK and 7 BUS were selected as research samples. The research results prove that: (1) Bank BCA Tbk and Bank BCA Syariah show significant differences in the NPL, LDR, ROA, BOPO, CAR and EVA ratios, while the NIM ratio does not show a significant difference; (2) Bank Mega Tbk and Bank Mega Syariah show significant differences in the NIM and EVA ratios, while the NPL, LDR, ROA, BOPO and CAR ratios do not show significant differences; (3) Bank BJB Tbk and Bank BJB Syariah show significant differences in the NPL, ROA, NIM, BOPO and EVA ratios, while the LDR and CAR ratios do not show significant differences; (4) Bank Pan Indonesia Tbk and Bank Panin Dubai Syariah show significant differences in the BOPO and EVA ratios, while the NPL, LDR, ROA, NIM and CAR ratios do not show significant differences; (5) Bank Victoria Internasional Tbk and Bank Victoria Syariah show significant differences in the NIM and CAR ratios, while the NPL, LDR, ROA, BOPO and EVA ratios do not show significant differences; (6) Bank KB Bukopin Tbk and Bank KB Bukopin Syariah show significant differences in NPL ratios, while the LDR, ROA, NIM, BOPO, CAR and EVA ratios do not show significant differences; (7) Bank BTPN Tbk and Bank BTPN Syariah show significant differences in the NPL, LDR, ROA, NIM, BOPO, CAR and EVA ratios.